Studi Religiusitas pada Anak-Anak Dari Orangtua Berbeda Agama - Anindita Karunia; Retno Hanggarani Ninin (Jurnal Pendidikan dan Kebudayaan Missio, 2022)
Interfaith marriage is a controversial marriage, either by religion or by the law that is applied in Indonesia. When interfaith couples marry and have children, how is the child’s religious life as one who was exposed to two different religious views? This research was conducted to depict religiosity in children with interfaith parents by using Glock & Stark’s five aspects of religiosity. Three respondents were involved and we use a qualitative approach for this research. All respondents have positive religious affect and religious knowledge. There’s uniqueness in their religious belief and religious practice, and two respondents have positive religious rituals